Gambaran Implementasi Aplikasi E-Kohort sebagai Media Pencatatan dan Pelaporan di Denpasar Selatan - Pradnyani, Putu Erma; Putra, Gede Wirabuana; Adiningsih, Luh Yulia; Putri, Putu Chrisdayanti Suada; Yuniati, Maria Gabriela; Punarbawa, Ida Bagus Wikrantha (Journal of Health Management Research, 2024)
Background: Maternal and child health is one part of the SDGs. The transformation of health technology requires the development and use of digitalization technology in the health sector. The e-KIA Cohort application was introduced in 2021 by the Ministry of Health and in 2022 it will only begin to be implemented in Denpasar City. However, until now there has been no research describing the implementation of e-Cohort in Denpasar City. Aims: : This research is to describe the implementation of the E-Cohort Application in recording and reporting in the South Denpasar. Methods: The method used in this research is descriptive qualitative. This qualitative research was carried out using an in-depth interview method adapted to the 5M theoretical approach, namely Man, Money, Method, Material and Machine. There were 5 informants for this research. Data processing was carried out using thematic analysis techniques. Results: Description of the implementation of the KIA e-Cohort from human factors. All informants have participated and received orientation regarding the E-Cohort application. The money factor shows that there is an orientation budget and an implementation budget. The method factor shows that there is an standard operational procedure created by each health facility. The machine factor shows that there are still obstacles in signal and data input infrastructure. Material factors show that the flow of using the e-cohort application is still accompanied by manual cohort filling and the use of this application is not yet used by all health workers in Denpasar so that the results of recording and reporting can be used optimally.. Conclusion: The implementation of the e-cohort application is already but there are still several obstacles. It is hoped that the development of this application can adapt to the situation and needs of users and that there will be training in using the E-Cohort application